THE INFLUENCE OF LIQUIDITY AND SALES GROWTH ON CAPITAL ADEQUACY RATIO IN SHARIA COMMERCIAL BANKS LISTED ON THE INDONESIAN STOCK EXCHANGE - -, Nur Wahidah; Damirah; Sahara, Ira (Institut Agama Islam Negeri Parepare, 2024)
The growth of the sharia banking industry in Indonesia has attracted the attention of both market players and regulators. Along with this growth, attention to the factors that influence the health and stability of Islamic banks has become increasingly important. One of the main indicators used to measure a bank's financial health is the capital adequacy ratio (CAR), which reflects the bank's ability to bear the risks that arise in its operations. This research aims to determine the effect of liquidity and sales growth on capital. Adequacy ratio in sharia commercial banks listed on the Indonesian stock exchange. This research uses an associative quantitative method with data collection techniques in the form of documentation using secondary data, and processing using SPSS version 25. The data analysis techniques for this research are classical assumption testing and hypothesis testing. The research results obtained show 1) Partial liquidity has a significant influence on the Capital Adequacy Ratio. This is proven by the t-test carried out, where the calculated t value (5.53) > t table (2.03) and a significant value of 0.000 < 0.05 are obtained. 2) Sales Growth has no significant influence on the Capital Adequacy Ratio. This is proven by the t-test carried out, where the calculated t value was obtained (-0.60) < t table (2.03) and a significant value of 0.549 > 0.05. 3) Simultaneously Liquidity and Sales Growth have a significant influence on the Capital Adequacy Ratio which has been proven from the F-Test results where the calculated f value (15.34) > f table (3.27) and a significant value of 0.00 < 0, are obtained. 05.